UAV and GIS based rapid earthquake-induced building damage assessment and methodology for EMS-98 isoseismal map drawing: The June 12, 2017 Mw 6.3 Lesvos (Northeastern Aegean, Greece) earthquake. (July 2019) - Mavroulis, Spyridon; Andreadakis, Emmanouil; Spyrou, Nafsika-Ioanna; Antoniou, Varvara; Skourtsos, Emmanouel; Papadimitriou, Panayotis; Kasssaras, Ioannis; Kaviris, George; Tselentis, Gerasimos - Akis; Voulgaris, Nikolaos; Carydis, Panayotis; Lekkas, Efthymios
Abstract: On June 12, 2017, an Mw 6.3 earthquake struck Lesvos Island (Northeastern Aegean, Greece). Building damage was observed in its southeastern part with very heavy structural damage limited in the settlement of Vrissa. Taking into account that Vrissa is located further inland from the epicenter than other settlements with less damage, Vrissa looks like an earthquake impact paradox. For interpreting this paradox, a complete approach for damage assessment in an earthquake-affected area was applied during the first hours of the emergency response phase in order to provide crucial information to civil protection agencies. It comprises integration of building-by-building inspection, use of desktop and web GIS applications, UAV survey and digital post processing, extraction of data and information related to the buildings of the affected area, application of the European Macroseismic Scale 1998 and assignment of macroseismic intensities. Correlation of the all aforementioned data with the geological, geomorphological, geotechnical and seismological properties of the affected area along with its buildings characteristics was followed. This damage scene is attributed to the synergy of the near-field location of Vrissa, recent deposits, geotechnically unstable zones, proximity to active faults, rupture directivity phenomena and vulnerable buildings. The integration of UAV and web GIS applications during a rapid post-earthquake field macroseismic reconnaissance can potentially be considered as a methodological framework that can be applied for similar analysis in other areas affected not only by earthquakes but also by other extreme events that have the potential to cause destructive effects on the natural environment, humans and infrastructures.